PENGARUH MEDIA PEMBELAJARAN SMART BOOKLET TERHADAP HASIL BELAJAR IPAS MATERI GAYA DI SEKITAR KITA PADA SISWA KELAS IV SDN DUKUH KUPANG V SURABAYA - Dwi Maharani, Putri Aprilia; Bahtiar, Reza Syehma; Noerhartati, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of fourth-grade students in the subject of science, especially on the material of forces around us. This is caused by the use of learning media that are less varied so that the learning process becomes less interesting and students are less active in understanding the material presented. This study aims to determine the effect of the use of Smart Booklet learning media on the learning outcomes of science on the material of forces around us in fourth-grade students of SDN Dukuh Kupang V Surabaya. This study uses a quantitative approach with an experimental method with a pretest–posttest control group design. The research subjects consisted of a control class and an experimental class. Data collection techniques were carried out through learning outcome tests given before (pretest) and after (posttest) learning. The results showed that in the control class the average pretest score was 69.83 and the average posttest score was 80.50, increasing by 10.67. Meanwhile, in the experimental class the average pretest score was 69.83 and the average posttest score was 86.17, increasing by 16.34. These results indicate that the increase in learning outcomes in the experimental class is higher than the control class. In addition, the results of the hypothesis test using the Independent Sample t-test show a significance value (Sig. 2-tailed) of 0.012 which is smaller than 0.05 so that H0 is rejected and H1 is accepted. Thus, it can be concluded that the use of Smart Booklet learning media has a significant and effective effect in improving the learning outcomes of science on the material of forces around us in grade IV students of SDN Dukuh Kupang V Surabaya.